The assessment of weight status in children and young people attending a spina bifida outpatient clinic: a retrospective medical record review - McPherson, Amy C.; Swift, Judy Anne; Yung, Emily; Lyons, Julia; Church, Paige (Informa Healthcare, 2013)
PURPOSE: Children with disabilities are two to three times more likely to become overweight or obese than typically developing children. Children with spina bifida (SB) are at particular risk, yet obesity prevalence and weight management with this population are under-researched. This retrospective chart review explored how weight is assessed and discussed in a children's SB outpatient clinic. METHOD: Height/weight data were extracted from records of children aged 2-18 with a diagnosis of SB attending an outpatient clinic at least once between June 2009-2011. Body mass index was calculated and classified using Centers for Disease Control and Prevention cut-offs. Notes around weight, diet and physical/sedentary activities were transcribed verbatim and analysed using descriptive thematic analysis. RESULTS: Of 180 eligible patients identified, only 63 records had sufficient data to calculate BMI; 15 patients were overweight (23.81%) and 11 obese (17.46%). Weight and physical activity discussions were typically related to function (e.g. mobility, pain). Diet discussions focused on bowel and bladder function and dietary challenges. CONCLUSIONS: Anthropometrics were infrequently recorded, leaving an incomplete picture of weight status in children with SB and suggesting that weight is not prioritised. Bowel/bladder function was highlighted over other benefits of a healthy body weight, indicating that health promotion opportunities are being missed. Implications for Rehabilitation It is important to assess, categorise and record anthropometric data for children and youth with spina bifida as they may be at particular risk of excess weight. Information around weight categorisation should be discussed openly and non-judgmentally with children and their families. Health promotion opportunities may be missed by focusing solely on symptom management or function. Healthcare professionals should emphasise the broad benefits of healthy eating and physical activity, offering strategies to enable the child to incorporate healthy lifestyle behaviours appropriate to their level of ability.